Rom und Mailand in der Spätantike. Repräsentationen städtischer Räume in Literatur, Architektur und Kunst - Fuhrer, Therese (Topoi, 2011)
The multidisciplinary contributions to this collection of papers look at Rome as the cultural and Milan as the political capital in the 4th and 5th centuries. In the literature of the time both cities were perceived as spaces in which the political and clerical power struggles, and the political and cultural changes which were so important for the Latin West took place. The cities are thereby understood as "stages" upon which the world theatre of the politics of power, culture and the church was produced. The reconstruction of both "stage settings" is based on texts, inscriptions and archaeological remains.; Therese Fuhrer, Freie Universität Berlin.